2010
DOI: 10.1080/13607863.2010.501063
|View full text |Cite
|
Sign up to set email alerts
|

Psychological resilience predicts depressive symptoms among spouses of persons with Alzheimer disease over time

Abstract: This study examines the three facets of psychological resilience (i.e., perceived control, commitment to living, challenge versus stability) as predictors of depressive symptoms over time among spousal caregivers of persons with Alzheimer disease; these resilience factors were considered over and above dementia-related and socio-demographic control variables. A sample of 105 cohabiting spouses of persons diagnosed with probable or possible Alzheimer disease was recruited for this study. Multilevel modeling ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
82
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 42 publications
8
82
0
1
Order By: Relevance
“…Our findings are in line with other studies, as we showed that moderate to higher levels of resilience were related to lower levels of depressive symptoms 3,27 . Resilience is a protective factor for depression associated with decreased stress 14 .…”
supporting
confidence: 83%
“…Our findings are in line with other studies, as we showed that moderate to higher levels of resilience were related to lower levels of depressive symptoms 3,27 . Resilience is a protective factor for depression associated with decreased stress 14 .…”
supporting
confidence: 83%
“…Conversely, life commitment was not a significant predictor of depression among caregivers. 27 A study that sought to describe the correlations between functionality, depressive symptomatology and cognition among groups of resilient and non-resilient elderly individuals found that resilience was negatively correlated with depressive symptomatology, thereby demonstrating that elderly individuals with high resilience exhibit less depressive symptomatology. 28 Depression, stress, overburden and psychological characteristics, as well as social, economic and family resources, have been significantly associated with resilience.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that resilience is associated with better physical and emotional conditions and the capacity to deal with adverse situations. 26 In Canada, O'Rourke et al 27 used a longitudinal study to analyze resilience (assessed through perceived control, life commitment and the challenge versus stability ratio) as a predictor of depressive symptoms among married caregivers over the course of a year (mean age of 69 years). In total, 58 of the caregivers were wives of individuals with (probable) Alzheimer's, while 47 of the caregivers were husbands of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The negative health consequences of looking after an older family member with dementia, particularly the effects on mental and physical health, are well documented. [5][6][7][8][9][10][11][12] People with dementia often have an array of neuropsychiatric symptoms, such as mood disorders, delusions, hallucinations, vegetative symptoms and psychomotor abnormalities.…”
Section: Introductionmentioning
confidence: 99%